2022
DOI: 10.3389/fimmu.2022.844262
|View full text |Cite
|
Sign up to set email alerts
|

Tick Intrastadial Feeding and Its Role on IgE Production in the Murine Model of Alpha-gal Syndrome: The Tick “Transmission” Hypothesis

Abstract: Recent studies have provided strong evidence indicating that lone star tick bites are a cause of AGS (alpha-gal syndrome, also known as red meat allergy RMA) in humans. AGS is characterized by an increase in IgE antibody production against galactose-alpha-1,3-galactose (aGal), which is a common glycan found in mammalian tissue, except in Old World monkeys and humans. The main causative factor of AGS, the lone star tick (Amblyomma americanum), is broadly distributed throughout the east and midwest of the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…This study also supports the previous study rejecting the aGal transmission hypothesis in AGS where the source of aGal in tick saliva was hypothesized from prior feeding on non-human mammalian hosts 14 . In our previous study using the mouse model with tick infestation, we observed that aGal levels in the mouse-fed ticks were low (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study also supports the previous study rejecting the aGal transmission hypothesis in AGS where the source of aGal in tick saliva was hypothesized from prior feeding on non-human mammalian hosts 14 . In our previous study using the mouse model with tick infestation, we observed that aGal levels in the mouse-fed ticks were low (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study using the mouse model with tick infestation, we observed that aGal levels in the mouse-fed ticks were low (Fig. S1 ) (see Supplementary Information) with highly varying levels of mouse antibodies specific to aGal 14 . While the alpha-1,3-galactosyltransferase orthologue gene has not been detected in ticks 23 , earlier research has indicated the potential involvement of other tick galactosyltransferases in the decoration of saliva with aGal.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 96 Meat from these animals is also believed to be safe for individuals with AGS to consume ( https://www.fda.gov/news-events/press-announcements/fda-approves-first-its-kind-intentional-genomic-alteration-line-domestic-pigs-both-human-food , accessed 11 April 2022). However, pre-clinical trials examining the safety of this meat using currently available animal models of alpha-gal syndrome 21 , 28 , 97 and clinical trials of this meat in human subjects need to be conducted.…”
Section: Clinical Implications Of Alpha-gal Syndromementioning
confidence: 99%
“…fda.gov/news-events/press-announcements/fda-approves-first-its-kind-intentional-genomic-alteration-line-domestic-pigsboth-human-food, accessed 11 April 2022). However, pre-clinical trials examining the safety of this meat using currently available animal models of alpha-gal syndrome 21,28,97 and clinical trials of this meat in human subjects need to be conducted. Alpha-gal sensitization has also been linked to coronary artery disease (CAD) with increased atherosclerotic burden and plaque instability.…”
Section: Cardiovascular/heart Diseasementioning
confidence: 99%